A Study of Pattern of Snake-Bite Cases Admitted to Hospitals in Bagalkot (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: The present study was under taken to know the Sociodemographic profile of snake bite victims.Methods: This is a Hospital based case series study which included snake bite cases of both sex groups and all agegroups who presented with history of snake bite or history of unknown bite with clinical features suggestiveof snake bite admitted to HSK Hospital and all private Hospitals of Bagalkot city in one year duration from 15thApril 2010 to 14th April 2011. Results: Of the 75 cases, maximum victims were males 61.4%. Maximum 60%victims belonged to 20-49 yrs age group. There was a statistically significant difference in the occurrence of casesin the age group of 20-49yrs and also among males of the same age group. Majority of victim 93.3% belongedto rural region which was statistically significant and 60% of the victims were farmers by occupation. Most ofthe bites 60% occurred in fields. Bites were more 37.3% between 12.01PM to 6PM and during monsoon season60.1%. Most common site of bite was foot 45.3%. Krait was the most commonly identified snake and most of itsbites were between 12.01AM to 6AM.
Keywords: Snake bite; Sociodemographic profile; Krait, season.